2002
DOI: 10.1002/1615-4169(200208)344:6/7<789::aid-adsc789>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis of Vinyl-Substituted Silicon Compounds with Dienes and Cycloalkenes

Abstract: Metathesis of 1,9‐decadiene and cyclooctene with trialkoxy‐ and trisiloxy‐substituted vinylsilanes in the presence of Grubbs catalyst leads to a formation of 1‐(silyl)deca‐1,9‐dienes and 1,10‐bis(silyl)deca‐1,9‐dienes. Under optimised conditions, the reaction is a convenient method for synthesis of disubstituted dienes and a model process for the development of syntheses of silylene(siloxylene)‐vinylene‐alkenylene copolymers via the metathesis transformations of divinyl‐substituted silicon compounds with termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Analysis of selected products (a) MeCl 2 SiCH@CHCH 2 OC 4 H 9 , collected fraction 119-123°C/1 mmHg, isolated yield 75%; 1 H NMR (C 6 D 6 , d, ppm): 0.49 (s, 3H, SiMe), 0.79-0.90 (m, 3H, CH 3 ), 1.27-1.53 (m, 4H, CH 3 CH 2 CH 2 ), 3.15-3.23 (m, 2H, CH 3 CH 2 CH 2 CH 2 O), 3.63-3.68 (m, 2H, OCH 2 CH@), 6.06 (dt, 1H, J = 18.5 Hz, 1.9 Hz, @CHSi), 6.33 (dt, 1H, J = 18.5 Hz, 3.6 Hz, @CHCH 2 O); 13 C NMR (C 6 D 6 ): 5.4 (SiMe), 14.3 (CH 3 ), 19.9 (CH 3 CH 2 ), 32.4 (CH 3 CH 2 CH 2 ), 70.9 (CH 3 CH 2 CH 2 CH 2 O), 71.7 (OCH 2 CH@), 122.8 (@CHSi), 150.4 (@CHCH 2 O); MS: m/z (rel. intensity) of ethoxy derivative: 61 (15), 77 (32), 89 (17), 95 (11), 101 (18), 103 (17), 105 (40), 117 (10), 119 (22), 129 (11), 131 (14), 133 (100), 134 (13), 143 (11), 145 (62), 146 (10), 147 (12), 173 (11), 189 (30), 191 (11), 205 (13), 131 (11), 233 (11), 237 (15).…”
Section: Procedures For the Synthesis Of Silylolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of selected products (a) MeCl 2 SiCH@CHCH 2 OC 4 H 9 , collected fraction 119-123°C/1 mmHg, isolated yield 75%; 1 H NMR (C 6 D 6 , d, ppm): 0.49 (s, 3H, SiMe), 0.79-0.90 (m, 3H, CH 3 ), 1.27-1.53 (m, 4H, CH 3 CH 2 CH 2 ), 3.15-3.23 (m, 2H, CH 3 CH 2 CH 2 CH 2 O), 3.63-3.68 (m, 2H, OCH 2 CH@), 6.06 (dt, 1H, J = 18.5 Hz, 1.9 Hz, @CHSi), 6.33 (dt, 1H, J = 18.5 Hz, 3.6 Hz, @CHCH 2 O); 13 C NMR (C 6 D 6 ): 5.4 (SiMe), 14.3 (CH 3 ), 19.9 (CH 3 CH 2 ), 32.4 (CH 3 CH 2 CH 2 ), 70.9 (CH 3 CH 2 CH 2 CH 2 O), 71.7 (OCH 2 CH@), 122.8 (@CHSi), 150.4 (@CHCH 2 O); MS: m/z (rel. intensity) of ethoxy derivative: 61 (15), 77 (32), 89 (17), 95 (11), 101 (18), 103 (17), 105 (40), 117 (10), 119 (22), 129 (11), 131 (14), 133 (100), 134 (13), 143 (11), 145 (62), 146 (10), 147 (12), 173 (11), 189 (30), 191 (11), 205 (13), 131 (11), 233 (11), 237 (15).…”
Section: Procedures For the Synthesis Of Silylolefinsmentioning
confidence: 99%
“…We have previously shown that Grubbs type catalysts effectively catalyse the cross-metathesis (CM) of trialkoxy-, trisiloxy-[8], trichloro-and generally electron withdrawing group substituted vinylsilanes [9] and vinylsilsesquioxanes [10] with styrenes, alkenes and numerous allyl derivatives. Metathesis of vinylsilanes with dienes and cycloalkenes catalysed by Grubbs type complexes has also been demonstrated [11]. Now, we would like to focus on the effect of substituents at silicon on the reaction, discuss advantages and drawbacks of cross-metathesis of vinylsilanes with olefins as a general synthetic method for the synthesis of vinyltrisubstituted silanes and finally search for a mechanistic scheme of catalysis of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…An analogous procedure was used for silylative coupling of 1,5-divinyltetramethyltrisiloxane (9) with styrene. Spectral data for (11). …”
Section: Silylative Coupling Of Vinyldimethylsiloxy-terminated Polydimentioning
confidence: 99%
“…In the chemistry of unsaturated organosilicon compounds effective metathesis transformations have been described by our group for vinyltris(trimethylsiloxy)silane [8,9], chlorosubstituted vinyldisiloxanes [9] and vinylsubstituted silsesquioxanes [10]. ViSi-(OEt) 2 OSi(OEt) 2 Vi (Vi = H 2 C@CH-) can be metathetically copolymerized with 1,9-decadiene [11,12] or divinylbenzene [13] and undergoes ROM/ADMET copolymerization with cyclooctadiene [11]. Divinyldisiloxanes were effectively converted in crossmetathesis with styrenes and 1-decene [14].…”
Section: Introductionmentioning
confidence: 99%
“…Related products from coupling more than one cycloalkene unit were also obtained. RORCM in competition with ROMP was observed in the cometathesis of vinylsilanes and cyclooctene [186]. RO Moderately regioselective RO-CM was observed in the metathesis of alkene 45 and allyltrimethylsilane [188].…”
Section: Nonpolymer-forming Ring Opening Metathesis Reactionsmentioning
confidence: 99%